2008
DOI: 10.1017/s1751731108001584
|View full text |Cite
|
Sign up to set email alerts
|

Goat’s αS1-casein polymorphism affects gene expression profile of lactating mammary gland

Abstract: Goat's a S1 -casein (CSN1S1) polymorphism has a significant effect on milk protein and lipid composition, which affects the nutritional quality and technological properties of milk. Moreover, this polymorphism has a large impact on the morphology of mammary epithelial cells. To explore the metabolic pathways modulated in relation to this polymorphism, we compared the mammary gene expression profiles of two groups of lactating goats carrying either two reference or two defective alleles, using a bovine oligonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
(41 reference statements)
2
9
0
1
Order By: Relevance
“…FAS of animal tissues is a homodimer, and each monomer carries seven catalytic domains and an acyl carrier protein in the following order: ketoacyl synthase, acetyl/malonyl transacylase, dehydratase, enoyl reductase, ketoacyl reductase, acyl carrier protein, and thioesterase . In the goat species, numerous studies have reported that FAS is regulated at the transcriptional level . Our study reveals that caprine FAS is also very likely regulated at the posttranslational level, according to the presence of up to 33 phosphosites through the entire protein backbone.…”
Section: Discussionmentioning
confidence: 74%
“…FAS of animal tissues is a homodimer, and each monomer carries seven catalytic domains and an acyl carrier protein in the following order: ketoacyl synthase, acetyl/malonyl transacylase, dehydratase, enoyl reductase, ketoacyl reductase, acyl carrier protein, and thioesterase . In the goat species, numerous studies have reported that FAS is regulated at the transcriptional level . Our study reveals that caprine FAS is also very likely regulated at the posttranslational level, according to the presence of up to 33 phosphosites through the entire protein backbone.…”
Section: Discussionmentioning
confidence: 74%
“…The first evidence of the effect of this genetic polymorphism on milk fat secretion arises from transcriptomic studies on mammary tissues. The expression levels of key lipogenic genes as well as genes known to influence membrane fluidity, cell-cell interaction, or chromatin organization are affected by the α s1 -CN genetic polymorphism in the goat (Ollier et al, 2008). Moreover, a study comparing FA profiles in goats displaying strong (A, B, and C alleles), or weak (F and G alleles) genotypes at the CSN1S1 locus demonstrated differences in proportions in milk fat of 17 FA, including the C8 to C12 SFA and palmitic, stearic, oleic, linoleic, and rumenic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The breeding values of the animals were estimated based on milk yield. Therefore, these differences are very important as they affect CSN1S1 and BLG genotypes on transcriptional level, milk yield, and proteins that have been reported (2,33-35). In addition, the differential expression between breeding value groups may be caused by genetic variation that is related to breeding value groups.…”
Section: Discussionmentioning
confidence: 99%